2021
DOI: 10.7150/jca.47863
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of CASC8 inhibits non-small cell lung cancer cells function and promotes sensitivity to osimertinib via FOXM1

Abstract: In a meta-analysis, the long noncoding RNA cancer susceptibility candidate 8 (CASC8) was found to be a cancer susceptibility gene closely related to lung cancer, but its functions in lung cancer are unknown. In the Cancer Genome Atlas database, the expression of CASC8 was significantly higher in non-small cell lung cancer than in adjacent normal tissues, and high expression of CASC8 was associated with poor prognosis in patients with lung ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Among the established 5 ferroptosis-related lncRNAs in this study, three have been found to be associated with tumor development. Silencing CASC8 inhibited the proliferation, migration, and invasion of non-small cell lung cancer cells and promoted their sensitivity to osimertinib [21]. LINP1 may be involved in the regulation of cell proliferation, cell adhesion and cell cyclerelated biological processes in early stage pancreatic ductal adenocarcinoma [22].…”
Section: Discussionmentioning
confidence: 99%
“…Among the established 5 ferroptosis-related lncRNAs in this study, three have been found to be associated with tumor development. Silencing CASC8 inhibited the proliferation, migration, and invasion of non-small cell lung cancer cells and promoted their sensitivity to osimertinib [21]. LINP1 may be involved in the regulation of cell proliferation, cell adhesion and cell cyclerelated biological processes in early stage pancreatic ductal adenocarcinoma [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our research, 8 m5C-related lncRNAs were carefully chosen via a bioinformatic method, 7 of which have never been previously studied in PDAC (AC022098.1, AL031775.1, AC005332.6, AC096733.3, AC025165.1, AC009974.1, and PAN3-AS1). Only the CASC8 has been reported in the multiple malignant tumor such as colorectal cancer, lung cancer, and hepatocellular carcinoma (37)(38)(39). We checked the above lncRNA expression in the human pancreatic ductal cell line and three pancreatic cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is crucial to the effective treatment of BC; however, it is limited by the development of chemoresistance [7,8,35]. Increasing evidence supports the idea that lncRNAs are key regulators of drug resistance [16,17]. Therefore, we examined the ability of EGFR-AS1 to act as a mechanism of resistance to the targeted drug docetaxel.…”
Section: Role Of Egfr-as1 Silencing In the Promotion Of Docetaxel Sensitivity In Bc Cellsmentioning
confidence: 99%
“…It has been reported that lncRNAs mediate cellular activities, including epithelial-to-mesenchymal transition (EMT), which is an important biological process in malignant tumor cells derived from epithelial cells and is bene cial for tumor growth, metastasis, invasion, and chemotherapy sensitivity [17][18][19]. Moreover, lncRNA EGFR antisense RNA 1 (EGFR-AS1) has been reported as an oncogenic molecule [15,20,21].…”
Section: Introductionmentioning
confidence: 99%